Relationship of Knowledge and Attitude Towards Dengue Prevention at Baiturrahman District Community - Azka Muda Adri; Kurnia Fitri Jamil; Rachmad Suhanda (Jurnal Ilmiah Mahasiswa Kedokteran Medisia, 2016)
Dengue hemorrhagic fever (DHF) is one of disease that often disturbs society because it can cause death. Dengue fever is transmitted by the bite of aedes aegypti and aedes albopictus that contain dengue virus. The prevention of dengue fever is preventing the bite of aedes aegypti and aedes albopictus that contain dengue virus to humans. One of way to prevent the dengue fever is keeping the environment clean so it will not be the breeding media for aedes aegypti and aedes albopictus, they are mosquito eradication and implementation of 3M (drain, close, and bury). Every single health problems, include the dengue hemorrhagic fever problem solving, behavioral factor is one of the most important thing. The Attention for the behavioral factors is the same as with the attention for to environmental factors, especially for the prevention disease. This research is an analytic observational with cross sectional design. Samples were taken in 1 March 2016 until 31 March 2016. The sample used the quota sampling technique for 96 respondents. The analysis showed a strong correlation between the level of knowledge (p value = 0,002) (rs = 0,695), attitude (p value = 0,002) (rs = 0,697) on dengue hemorrhagic fever prevention for society in Baiturrahman. It is concluded that there is a strong relation between knowledge and attitudes to the dengue hemorrhagic fever prevention action for society in Baiturrahman. More knowledge can be a better action to prevent the dengue hemorrhagic fever, A better attitude can be a better way for dengue hemorrhagic fever prevention for the society in Baiturrahman.